cRel expression regulates distinct transcriptional and functional profiles driving fibroblast matrix production in systemic sclerosis - Worrell, Julie C.; Leslie, Jack; Smith, Graham R.; Zaki, Marco Y. W.; Paish, Hannah L.; Knox, Amber; James, Michelle L.; Cartwright, Tyrell N.; O'Reilly, Steven; Kania, Gabriela; Distler, Oliver; Distler, Jörg; et al. (Rheumatology, 2020)
Objectives. NF-kappa B regulates genes that control inflammation, cell proliferation, differentiation and survival. Dysregulated NF-kappa B signalling alters normal skin physiology and deletion of cRel limits bleomycin-induced skin fibrosis. This study investigates the role of cRel in modulating fibroblast phenotype in the context of SSc.
CRIS-Team WoS Importer:2021-01-29